Controlling the mechanical properties of hydrogels via modulating the side-chain length. Issue 16 (14th April 2023) - Kureha, Takuma; Takahashi, Kazuma; Kino, Mion; Kida, Hikaru; Hirayama, Takuto
Abstract : Even though the toughness of hydrogels is usually adjusted by changing the cross-linking density and structure, or the polymer concentration, we have discovered a new strategy to control the toughness via modulating the side-chain length. Abstract : Even though the toughness of hydrogels is usually adjusted by changing the cross-linking density and structure, or the polymer concentration, we have discovered a new strategy to control the toughness via modulating the side-chain length. In this study, this strategy was applied to biocompatible poly(oligo(ethylene glycol) methyl ether methacrylate) with long ethylene-oxide side chains.